2017
DOI: 10.1017/s0022109017000588
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Fund Managers Identify and Share Profitable Ideas?

Abstract: We study data from an organization in which fund managers privately share and discuss detailed investment recommendations. Buy recommendations generate positive abnormal returns, and sell recommendations result in negative abnormal returns. In the context of these results, we explore an important economic question: Why do skilled investors share profitable ideas with others? Evidence suggests that the managers in our sample share to receive feedback on their ideas and to attract additional arbitrageur capital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(16 citation statements)
references
References 26 publications
1
14
1
Order By: Relevance
“…Many people share investment opinions on the web. Existing research shows that some of these investment-related online postings contain informational value, whereas others do not (e.g., Antweiler and Frank, 2004;Das and Chen, 2007;Chen et al, 2014;Crawford et al, 2017). Regulators around the globe have repeatedly expressed concerns about individual investors' executing costly trades based on investment-related online postings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many people share investment opinions on the web. Existing research shows that some of these investment-related online postings contain informational value, whereas others do not (e.g., Antweiler and Frank, 2004;Das and Chen, 2007;Chen et al, 2014;Crawford et al, 2017). Regulators around the globe have repeatedly expressed concerns about individual investors' executing costly trades based on investment-related online postings.…”
Section: Introductionmentioning
confidence: 99%
“…These studies report mixed results. Whereas some papers document that there is a statistically significant and economically meaningful relation between opinions posted in online communities and future returns (e.g., Chen et al, 2014;Avery et al, 2016;Crawford et al, 2017), others find no such relationship (e.g., Tumarkin and Whitelaw, 2001;Dewally, 2003;Antweiler and Frank, 2004;Das and Chen, 2007;Kim and Kim, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Colla and Mele [13] found that closely related investor behaviors in the information networks are more likely to produce herd effects. Sharing private information among fund managers is the rational choice for maximizing their own interests [14]. Moreover, the topological structure characteristics of the social networks among fund managers can affect the effectiveness of information exchange and risk contagion [15].…”
Section: Introductionmentioning
confidence: 99%
“…Players face a simple tradeoff: concealing new information gives them a relative information advantage that translates into a payoff advantage, but it also breaks the feedback loop for future sharing, and they forego the chance to generate more information which increases absolute payoffs even when there is no disparity in those payoffs. Stein (2008) shows that if the probability 1 These settings include the steel minimills industry (von Hippel, 1987;Schrader, 1991), the semiconductor industry (Appleyard, 1996), academic research (Bouty, 2000;Häussler, 2011;Häussler et al, 2014), and financial investment (Crawford et al, 2017;Botelho, 2018;Rantala, forthcoming).…”
Section: Introductionmentioning
confidence: 99%
“…Our paper contributes to the literature in a number of ways. In the context of finance, Crawford et al (2017), Botelho (2018), and Rantala (forthcoming) provide evidence of information sharing among investment professionals. Our results contribute to this literature that studies the mechanisms behind the empirical phenomenon of correlated trading (e.g., Duffie and Manso, 2007;Colla and Mele, 2010;Manela, 2014;Andrei and Cujean, 2017) by providing a more nuanced picture of individuals' incentives and a direct test of one of the key theoretical arguments (Stein, 2008).…”
Section: Introductionmentioning
confidence: 99%